Novel regulation of melanogenesis by adiponectin via the AMPK/CRTC pathway. (14th July 2017) - Bang, Seunghyun; Won, Kwang Hee; Moon, Hye‐Rim; Yoo, Hanju; Hong, Areum; Song, Youngsup; Chang, Sung Eun
Summary: Several studies observed that adiponectin, an important adipokine that improves glucose metabolism by regulating AMP‐activated protein kinase (AMPK) signaling, is dermatologically beneficial. In our recent microarray data, we found that adiponectin expression was lower in lesional skin than in non‐lesional skin of melasma patients. Given that AMPK is a key adiponectin signaling mediator, we investigated the role of adiponectin and AICAR, a cell‐permeable AMPK activator, in melanogenesis. We herein showed that adiponectin and AICAR downregulated MITF, tyrosinase, TRP‐1, and DCT expression and reduced melanin content in normal human and mouse melanocytes. The depigmenting effect of adiponectin was mediated via AMPK activation, which induced the inhibitory phosphorylation of CREB‐regulated transcription co‐activators (CRTCs) and subsequent suppression of the novel CRTC/CREB pathway in melanocytes. These findings suggest that adiponectin and its analogs are useful as a clinical strategy for treating hyperpigmentation disorders.